2020
DOI: 10.1002/agg2.20083
|View full text |Cite
|
Sign up to set email alerts
|

How does tillage intensity affect chemical soil health indicators? A United States meta‐analysis

Abstract: Tillage intensity can affect chemical soil health indicators either positively or negatively depending on inherent soil properties and management practices. Soil chemical data (total N, P, K, Ca, Mg, and pH) from four depth increments within 196 published studies were compiled and subjected to a meta-analysis comparing chisel plow (CP), no-till (NT), and perennial systems (PER) with moldboard plowing (MP). Overall, CP did not affect soil chemical indicators when compared to MP, but converting from MP to NT inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Soil pH did not differ among cultivated fields and averaged 6.31, but pH was found to be significantly lower in hayfields (5.90) (Supporting Information: Table ). In earlier studies, soil pH was found to be the lowest under NT systems (Dick, 1983), but a recent meta‐analysis (Nunes, Karlen, Moorman, et al, 2020) of tillage effects on soil chemical properties found no pattern of decreasing soil pH under NT systems. These silt loam soils are naturally acidic, and cultivated fields receive regular inputs of lime to maintain a pH above 6.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Soil pH did not differ among cultivated fields and averaged 6.31, but pH was found to be significantly lower in hayfields (5.90) (Supporting Information: Table ). In earlier studies, soil pH was found to be the lowest under NT systems (Dick, 1983), but a recent meta‐analysis (Nunes, Karlen, Moorman, et al, 2020) of tillage effects on soil chemical properties found no pattern of decreasing soil pH under NT systems. These silt loam soils are naturally acidic, and cultivated fields receive regular inputs of lime to maintain a pH above 6.…”
Section: Resultsmentioning
confidence: 95%
“…Using the measured soil properties of TC, TN, SOM and BD, boxplots according to tillage at the 0–15 cm soil depth (Figure 2) revealed large differences between hayfields and tilled fields; however, there was little difference among the tilled fields. A meta‐analysis of tillage types by Nunes, Kurlen, Moorman et al (2020) determined that perennial systems such as hayfields increase TN in surface soil (0–15 cm) compared to MP after more than 2 years. At the deeper soil depth, boxplots (Figure 2) revealed similar concentrations of SOM, TC and TN between hayfields and MP, while NT soils had the lowest amounts.…”
Section: Resultsmentioning
confidence: 99%
“…Tillage also influences soil chemical fertility but often not exactly in the way it was intended. Notably, it has been observed that topsoil total N, P, and K concentrations decrease, particularly under the harsher tillage operations in comparison to no tillage, as a metaanalysis by Nunes et al has shown [196]. This effect on the primary nutrients is explained because tillage expedites SOM oxidation, thus boosting nutrient release in plant-available forms, which are, nevertheless, also more easily lost by leaching and gas emission [197] whether the adequate conditions are met, which it seems the most likely [196].…”
Section: Tillage and Soil Health In Vineyardsmentioning
confidence: 99%